Smart Government: Village Development Strategy 4.0 Based on the Millennial Generation - Ni Luh Yulyana Dewi; I Wayan Joniarta; Ni Putu Yunita Anggreswari (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2022)
To improve the quality of the millennial generation to become superior human resources and also as the main actor of development, including in the development of tourist villages, the smart village model is an innovative solution that puts forward innovation and technology utilization to transform villages into independent ones with a better quality of life for the community, so that it is expected to reduce the pace of urbanization and reduce the digital divide in Indonesia. This study's objective is to outline a tourism village development strategy 4.0 focused on the millennial generation. The research method employed was qualitatively descriptive research. Observation, interviews, and documentation were employed to obtain information for this study. This research utilizes both primary and secondary data sources. In this study, qualitative data analysis approaches were employed to analyze the data. The findings revealed that the contribution of the millennial generation in the development of the Carangsari Tourism Village occurred in three phases: the procedure phase, the process phase, and the digitization phase. By actively promoting and engaging in events that can make Carangsari a nationally competitive tourist village, the millennial generation plays a significant role in the development of tourist villages.